The effect of mouse strain on herpes simplex virus type 1 (HSV-1) infection of the central nervous system (CNS) - Kastrukoff, Lorne F (BioMed Central, 2012)
BACKGROUND: Mice infected with HSV-1 can develop lethal encephalitis or virus induced CNS demyelination. Multiple factors affect outcome including route of infection, virus and mouse strain. When infected with a sub-lethal dose of HSV-1 strain 2 via the oral mucosa, susceptible SJL/J, A/J, and PL/J mice develop demyelinating lesions throughout the brain. In contrast, lesions are restricted to the brainstem (BST) in moderately resistant BALB/c mice and are absent in resistant BL/6 mice. The reasons for the strain differences are unknown. METHODS: In this study, we combine histology, immunohistochemistry, and in-situ hybridization to investigate the relationship between virus and the development of lesions during the early stage (< 24 days PI) of demyelination in different strains of mice. RESULTS: Initially, viral DNA and antigen positive cells appear sequentially in non-contiguous areas throughout the brains of BALB/c, SJL/J, A/J, and PL/J mice but are restricted to an area of the BST of BL/6 mice. In SJL/J, A/J, and PL/J mice, this is followed by the development of 'focal' areas of virus infected neuronal and non-neuronal cells throughout the brain. The 'focal' areas follow a hierarchical order and co-localize with developing demyelinating lesions. When antigen is cleared, viral DNA positive cells can remain in areas of demyelination; consistent with a latent infection. In contrast, 'focal' areas are restricted to the BST of BALB/c mice and do not occur in BL/6 mice. CONCLUSIONS: The results of this study indicate that susceptible mouse strains, infected with HSV-1 via the oral mucosa, develop CNS demyelination during the first 24 days PI in several stages. These include: the initial spread of virus and infection of cells in non-contiguous areas throughout the brain, the development of 'focal' areas of virus infected neuronal and non-neuronal cells, the co-localization of 'focal' areas with developing demyelinating lesions, and latent infection in a number of the lesions. In contrast, the limited demyelination that develops in BALB/c and the lack of demyelination in BL/6 mice correlates with the limited or lack of 'focal' areas of virus infected neuronal and non-neuronal cells in these two strains.